Developing the Australian Midwifery Workplace Culture instrument. Issue 1 (5th November 2019) - Catling, Christine; Rossiter, Chris; McIntyre, Erica
Abstract: Aim: To develop and psychometrically test the Australian Midwifery Workplace Culture instrument. Background: Workplace culture is critical within midwifery settings. Culture determines not only the well‐being and continued retention of maternity staff and managers but it also affects the quality and ultimate safety of the care they provide to women, infants and families. Several studies have identified cultural problems within maternity services. Relatively few instruments take account of the unique aspects of these workplaces and the relationship between midwives and women. Design: Three‐stage instrument development involved item generation (based on the Culture of Care Barometer), expert content validation and a pilot test. Methods: During 2016, 38 midwifery experts reviewed the initial items, and 322 midwives then pilot‐tested the draft instrument. We used exploratory factor analysis to identify key domains and to refine the instrument. Results: The refined instrument contained 22 items in three distinct domains: relationship with managers, empowerment and collegiality. Conclusion: The instrument can contribute to understanding important dimensions of the culture in maternity workplaces and thus to examining problematic attitudes and practices. The instrument requires further development and testing with larger and more diverse samples of midwives and validation in specific midwifery settings and models of care. SUMMARY STATEMENT: What is already known about this topic? Previous research reports problems in the organizational culture in maternity services, increasing the stress on midwives and potentially affecting the care they provide to women and infants. Negative workplace culture may contribute to attrition in maternity workforce. There are few measures that specifically address midwifery workplace culture. What this paper adds? This paper presents a new instrument designed to measure dimensions of midwifery workplace culture, detailing item generation and pilot testing. Analysis identified three domains that demonstrated good psychometric properties: relationship with management; empowerment and autonomy; collegiality and relationship with peers. Implications of this paper: The exploratory factor analysis suggests the utility of this instrument for assessing workplace culture in midwifery settings. The study recommends further testing of this instrument and validation in diverse midwifery workplaces, including large and small hospitals, community services and rural and remote areas.